PENERAPAN PAJAK PERTAMBAHAN NILAI ATAS BARANG HASIL PERTANIAN TERHADAP PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 70P/HUM/2013: Fitria Ratna Wardika - Wardika, Fitria Ratna (Reformasi Hukum, 2016)
Basically all goods and services are Taxable Goods and Taxable Services, thus subject to Value Added Tax (VAT). However, there are some goods or services that obtain facilities exempted from the imposition of VAT, one of which is agricultural goods which is one of certain Taxable Goods which is strategic as stipulated in Government Regulation Number 12 Year 2001 concerning the Import and / or Delivery of Taxable Goods Specific Taxes that are Strategic as already amended several times and the latest by Government Regulation Number 31 Year 2007 (PP 31/2007). In relation to the VAT treatment of agricultural products, the Indonesian Chamber of Commerce (KADIN) has applied for a judicial review of several provisions of PP 31/2007 against the VAT Act. Furthermore, pursuant to Supreme Court Decision Number 70P / HUM / 2013, the Supreme Court has granted a petition for judicial review of the provisions of PP 31/2007 to the VAT Act filed by the Chamber of Commerce. The implications of the Supreme Court ruling resulted in a significant number of provisions and implementation of VAT on agricultural goods. The application of VAT on agricultural goods based on Government Regulation 12/2001 and its amendments, namely on the delivery of certain Taxable Goods which are strategic in the form of agricultural goods, are exempted from the imposition of VAT, while the application of VAT on agricultural goods after the Supreme Court Decision Number 70P / HUM / 2013, ie on the delivery and / or import of agricultural goods, owed VAT. The consequences of law / implication of the Decision of the Supreme Court of the Republic of Indonesia Number 70P / HUM / 2013 are: 1) from the legal aspect (substance), the agricultural goods become Taxable Goods 2) from the legal aspect (regulation), the Government needs to do refinement of Government Regulation No. 12/2001 and its amendment, 3) from the aspect of tax administration, there will be potential addition of Input Tax. ABSTRAK Pada dasarnya semua barang dan jasa merupakan Barang Kena Pajak dan Jasa Kena Pajak, sehingga dikenakan Pajak Pertambahan Nilai (PPN). Namun demikian, ada beberapa barang atau jasa yang mendapatkan fasilitas dibebaskan dari pengenaan PPN,salah satunya yaitu barang hasil pertanian yang merupakan salah satu Barang Kena Pajak tertentu yang bersifat strategis sebagaimana diatur dalam Peraturan Pemerintah Nomor 12 Tahun 2001 tentang Impor dan/atau Penyerahan Barang Kena Pajak Tertentu yang Bersifat Strategis sebagaimana telah beberapa kali diubah terakhir dengan Peraturan Pemerintah Nomor 31 Tahun 2007 (PP 31/2007). Sehubungan dengan perlakuan PPN atas barang hasil pertanian tersebut, Kamar Dagang Indonesia (KADIN) telah melakukan permohonan uji materiil atas beberapa ketentuan PP 31/2007 terhadap Undang-Undang PPN. Selanjutnya, berdasarkan Putusan Mahkamah Agung Nomor 70P/HUM/2013, Mahkamah Agung telah mengabulkan permohonan uji materiil atas ketentuan PP 31/2007 terhadap Undang-Undang PPN yang diajukan oleh KADIN. Implikasi dari adanya Putusan Mahkamah Agung tersebut, mengakibatkan terjadinya perubahan sejumlah ketentuan dan penerapan yang cukup signifikan mengenai PPN atas barang hasil pertanian. Penerapan PPN terhadap barang hasil pertanian berdasarkan Peraturan Pemerintah 12/2001 dan perubahannya, yaitu atas penyerahan Barang Kena Pajak Tertentu yang bersifat strategis berupa barang hasil pertanian, dibebaskan dari pengenaan PPN, sedangkan penerapan PPN terhadap barang hasil pertanian setelah adanya Putusan Mahkamah Agung Republik Indonesia Nomor 70P/HUM/2013, yaitu atas penyerahan dan/atau impor barang hasil pertanian, terutang PPN. Adapun akibat hukum/impikasi dari Putusan Mahkamah Agung Republik Indonesia Nomor 70P/HUM/2013 tersebut yaitu: 1) dari aspek legal (substansi), maka barang hasil pertanian menjadi termasuk Barang Kena Pajak 2) dari aspek legal (regulasi), Pemerintah perlu melakukan penyempurnaan terhadap Peraturan Pemerintah Nomor 12/2001 beserta perubahannya, 3) dari aspek administrasi perpajakan, maka akan timbul potensi penambahan Pajak Masukan.